Characterisation and geographical traceability of Italian goji berries. (1st March 2019) - Bertoldi, Daniela; Cossignani, Lina; Blasi, Francesca; Perini, Matteo; Barbero, Alice; Pianezze, Silvia; Montesano, Domenico
Highlights: Goji berries produced in Italy and in Asia were studied. Stable isotopic ratios, elemental and carotenoid profiles of goji were obtained. Discriminant analysis was used to distinguish Italian and Asian samples. The investigated parameters can be considered useful geographic origin markers. Abstract: This work characterises and distinguishes Italian and Asian goji berries, combining three analytical approaches to determine 5 light stable isotope ratios, 57 mineral elements and 14 carotenoids. The study analyses stable isotope ratios and provides full HPLC-DAD-MS characterisation of the carotenoid fraction in goji berries for the first time. The isotopic composition of Italian berries was characterised by δ 13 C values ranging between −28.2‰ and −25.7‰, δ 15 N between 2.3 and 7.3‰, δ 34 S between 2.6 and 7.9‰, and D/H between −112 and −49‰. Italian goji berries were shown to have a particular composition and interesting nutritional characteristics, specifically a higher total carotenoid content (355 mg/100 g dw mean content vs 198 mg/100 g dw) and higher content of some micronutrients: K, B, Cu, Mo, Se, and Zn. On the basis of δ 34 S, Y, U, Cu, Rb, zeaxanthin palmitate and total carotenoid content, discriminant analysis correctly classified all samples according to their geographical origin.